A NEW CONTRIBUTION TO UNDERSTANDING LATE HOLOCENE ENVIRONMENTAL DYNAMICS IN THE SOUTHEASTERN PAMPA PLAIN, ARGENTINA: A MULTI-INDICATOR ANALYSIS OF LAGUNA LAS MOSTAZAS (Ameghiniana, 2024)
A multi-indicator analysis, including diatoms, mollusks, pollen and non pollen palynomorphs (NNPs) was performed to reconstruct Las Mostazas lake environmental history during the Late Holocene, in order to provide detailed paleoenvironmental new data for the southeastern Pampa plain. The record indicates the presence of a lake since ca. 3,400 cal. yr BP to the present. At the base of the record, between ca. 3,400 and 3,200 – 3,100 cal. yr BP and under a regional dry environment, a shallow, clear and brackish environment, subjected to intermittent/ephemeral regimes intercalated with episodes of total desiccation was developed. The lake evolved into a fresh and brackish shallow lake towards ca. 2,200 cal. yr BP, in which shallowness conditions are suggested by most indicators, but a briefly moment of higher water level at ca. 2,200 – 2,000 cal. yr BP is detected and turbidity begins to increase. Freshwater conditions installed ca. 1,700 – 1,600 cal. yr BP in a deeper and turbid lake. Periods of intense rainfall, that would have started at ca. 2,000 cal. yr BP, and intensified at ca. 1,500 – 1,200 cal yr BP may have promoted high water levels and the input of organic matter into the lake. In the last ca. 600 cal. yr BP lake became to configure like modern one. During the last ca. 80 years (1930 – 2009 CE), a process of accelerated eutrophication has been registered in the lake. In general terms, the evolution of the Las Mostazas lake agrees with the model proposed for other lakes of the southeastern Pampa plain.